Performance of Female Thin Tail Sheep Fed Ration Containing Fermented Shrimp Waste by EM-4 - Ibnul Abror Musthofa; Budi Ayuningsih; Iman hernaman (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2022)
The use of shrimp waste as ruminant feed is constrained by the presence of chitin which is difficult to digest. This study aimed to determine the use of shrimp waste fermented with EM-4 as additional feed for female Thin Tailed sheep. A total of 18 female Thin-Tailed sheep with a body weight of 10.35Â±0.88 kg were allocated to 3 ration treatments containing fermented shrimp waste with EM-4, namely 5%, 7.5% and 10%. The sheep were kept for 90 days at CV. Bungah Tani Djaya's Livestock to measure its performance. The results showed that the use of fermented shrimp waste up to 10% did not interfere with the performance of femaleThin-Tailed sheep with the average dry matter consumption, crude protein consumption, total digestible nutrient (TDN) consumption, daily body weight gain, and feed conversion were 340,29 g/head/day, 31.68 g/head/day, 195.63 g/head/day, 61.80 g/head/day, and 6.18 respectively. The results of the study concluded that the use of shrimp waste fermented with EM-4 up to 10% can be used as additional feed for female Thin-Tailed sheep.